Rekonstruksi Rencana Pelaksanaan Pembelajaran dan Pengembangan Keterampilan Menulis Teks Anekdot bagi Siswa SMA/MA di Era Merdeka Belajar - Novi Auliana Putri; Arinal Hasanah; Indra Rasyid Julianto; Wagiran Wagiran; Deby Luriawati Naryatmojo (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This article aims to find out how the quality of the items and assessment rubrics on aspects of language skills, namely the writing skills of students in class X SMA / MA in the odd semester Indonesian language lessons anecdotal text material located in Kudus. Researchers reconstructed the items and assessment rubrics and developed the learning media that would be delivered to students. The KD taken in this study were KD 3.5 for the realm of knowledge and KD 4.5 in the realm of anecdotal text material skills. The research that the researcher makes is included in the form of descriptive-qualitative research. The techniques in data collection that the researchers used in making this article include: reading and writing techniques and analysis techniques with data reduction, presenting existing data, and drawing conclusions. Furthermore, the results found that the lesson plans of Indonesian language teachers at SMA/MA Kudus did not meet the criteria for the assessment of the three aspects, namely material, construction, and language. The first aspect is the material reaches 70%, construction 70%, and language 75%. In addition, the assessment rubric which was originally still in the cognitive domain was reconstructed by changing to the skill or psychomotor domain. The last result is the development of media used by teachers, researchers develop learning media so that students' skills in writing anecdotal texts can be achieved through the existence of android-based learning applications in the era of independent learning, especially in anecdotal texts. So that the learning objectives in the era of independent learning can be achieved optimally.